Analysis of the Degree of Soil Contamination by Metallic Trace Elements Used During the Establishment of an Industrial Company in the Fields of Electricity, Electronics, and Automotive Mechanics: Study of the Kachoma District in the City of Kipushi/Haut-Katanga (DR Congo) - Jacques, Mwila Sompwe; Patrice, Tabu Kiwele; Peguy, Mututa Ilunga; Immaculee, Mahongo Kalumbu; Ephraime, Musale Muyabala; Anicet, Mwewa Ndimina (International Journal of Scientific Research and Management (IJSRM), 2024)
The objective of this research was to assess the level of soil pollution in the Kachoma district located around the former discharge basin (dike 1) of the Générale desquarries et des mines/Kipushi (Gécamines/Kipushi). The samples were taken from two sites (OUA 1 and the cell five years) using a manual auger at a depth of 20 cm to 40 cm and packaged in a plastic bag before being analyzed in the laboratory. The Cu, Co, Ni, Pb, and Zn content was determined by an Inductively Coupled Plasma (ICP) spectrometer. The results showed that the soils sampled in the two cells were largely polluted by Cu, Zn, Pb, Mn, and Co. It is, therefore, imperative to see how to remedy the soil pollution of the Kachoma district.